The Effectiveness of Group Guidance with Modelling in Increasing The Maturity of Career Choice - Sisri Wahyuni; A. Muri Yusuf; Z. Mawardi Efendi (International Journal of Research in Counseling and Education, 2017)
The maturity of the career choice direction becomes a central idea in the career development of the students. There are still many students who are less thorough in understanding career information. Therefore, the purpose of this study is to look at the effectiveness of group counseling services with modelling in improving student career choices. The research used quasi experimental approach through the design of non equivalent control group. Research subjects seven students experimental group and seven students control group. This research used career maturity choice with reliability 0.86. Then the data were analyzed using Wilcoxon Signed Ranks Test and Kolmogorov Smirnov 2 Independent Samples and Normalized Gain Scores. The result shows that group counseling service with modelling effective for increase the career maturity choices